2011
DOI: 10.1590/s1679-45082011ao1833
|View full text |Cite
|
Sign up to set email alerts
|

Role of adipose tissue-derived stem cells in the progression of renal disease

Abstract: Objective: To analyze the role of adipose tissue-derived stem cells in reducing the progression of renal fibrosis. Methods: adipose tissue-derived stem cells were isolated from C57Bl/6 mice and characterized by cytometry and differentiation. Renal fibrosis was established after unilateral clamping of the renal pedicle for 1 hour. Four hours after reperfusion, 2.105 adipose tissue-derived stem cells were administered intraperitoneally and the animals were followed for 24 hours during 6 weeks. In another experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…There were great differences in the types and sources of stem cells. Adipose Tissue-Derived Mesenchymal Stem Cells (ADMSCs) were derived from SD rats ( Chen et al, 2011 ; Gao et al, 2012 ; Masoud et al, 2012 ; Shih et al, 2013 ; Sheashaa et al, 2016 ; Zhou et al, 2016 ; Lam et al, 2017 ; Zhang et al, 2017 ; Changizi-Ashtiyani et al, 2020 ), Wistar rats ( Wang et al, 2013 ; Hussein et al, 2016 ; Zhao et al, 2016 ; Shi et al, 2018 ; Awadalla et al, 2021 ), humans ( Zhou et al, 2017 ; Huang et al, 2020 ), Fisher 344 rats ( Feng et al, 2010 ) and C57BL/6 mice ( Donizetti-Oliveira et al, 2011 ; Donizetti-Oliveira et al, 2012 ; Furuichi et al, 2012 ). Bone Marrow Derived Mesenchymal Stem Cells (MDMSCs) were derived from Lewis rats ( Erpicum et al, 2017 ), Wister rats ( Semedo et al, 2009 ; Havakhah et al, 2018 ), SD rats ( Lange et al, 2005 ; Wang et al, 2005 ; Wang and Fu, 2008 ; Tögel et al, 2009 ; Zhuo et al, 2011 ; Altun et al, 2012 ; Huang et al, 2012 ; Zhuo et al, 2013 ; Cai et al, 2014a ; Cai et al, 2014b ; Zhao et al, 2014 ; Wang et al, 2019 ), C57BL/6 mice ( Liu et al, 2011 ; Qi et al, 2014 ; Xie et al, 2015 ; Hu et al, 2016 ), BALB/C mice ( Xing et al, 2014 ), Rabbits ( Yang et al, 2008 ; Fang, 2009 ), Sheep ( Behr et al, 2007 ; Behr et al, 2009 ) and human ( Cao et al, 2010 ; Wise et al, 2014 ; Collett et al, 2017b ; Zilberman-Itskovich et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were great differences in the types and sources of stem cells. Adipose Tissue-Derived Mesenchymal Stem Cells (ADMSCs) were derived from SD rats ( Chen et al, 2011 ; Gao et al, 2012 ; Masoud et al, 2012 ; Shih et al, 2013 ; Sheashaa et al, 2016 ; Zhou et al, 2016 ; Lam et al, 2017 ; Zhang et al, 2017 ; Changizi-Ashtiyani et al, 2020 ), Wistar rats ( Wang et al, 2013 ; Hussein et al, 2016 ; Zhao et al, 2016 ; Shi et al, 2018 ; Awadalla et al, 2021 ), humans ( Zhou et al, 2017 ; Huang et al, 2020 ), Fisher 344 rats ( Feng et al, 2010 ) and C57BL/6 mice ( Donizetti-Oliveira et al, 2011 ; Donizetti-Oliveira et al, 2012 ; Furuichi et al, 2012 ). Bone Marrow Derived Mesenchymal Stem Cells (MDMSCs) were derived from Lewis rats ( Erpicum et al, 2017 ), Wister rats ( Semedo et al, 2009 ; Havakhah et al, 2018 ), SD rats ( Lange et al, 2005 ; Wang et al, 2005 ; Wang and Fu, 2008 ; Tögel et al, 2009 ; Zhuo et al, 2011 ; Altun et al, 2012 ; Huang et al, 2012 ; Zhuo et al, 2013 ; Cai et al, 2014a ; Cai et al, 2014b ; Zhao et al, 2014 ; Wang et al, 2019 ), C57BL/6 mice ( Liu et al, 2011 ; Qi et al, 2014 ; Xie et al, 2015 ; Hu et al, 2016 ), BALB/C mice ( Xing et al, 2014 ), Rabbits ( Yang et al, 2008 ; Fang, 2009 ), Sheep ( Behr et al, 2007 ; Behr et al, 2009 ) and human ( Cao et al, 2010 ; Wise et al, 2014 ; Collett et al, 2017b ; Zilberman-Itskovich et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…①1 day after administration: 36 studies were included for data analysis ( Chen et al, 2011 ; Erpicum et al, 2017 ; Guo and Wang, 2018 ; Ryoun et al, 2014 ; Bo et al, 2013 ; Zhuo et al, 2013 ; Liang et al, 2015 ; Behr et al, 2009 ; Gupta et al, 2015 ; Sadek et al, 2013 ; Rodrigues et al, 2017 ; Tian et al, 2017 ; Havakhah et al, 2018 ; Behr et al, 2007 ; Cai et al, 2014b ; Zhuo et al, 2011 ; Hu et al, 2013 ; Cao et al, 2010 ; La Manna et al, 2011 ; Xing et al, 2014 ; Hussein et al, 2016 ; Awadalla et al, 2021 ; Zhou et al, 2016 ; Zhao et al, 2014 ; Chen et al, 2013 ; Donizetti-Oliveira et al, 2011 ; Fahmy et al, 2017 ; Hattori et al, 2015 ; Zhao et al, 2016 ; Tsuda et al, 2014 ; Li et al, 2015 ; Gao et al, 2012 ; Altun et al, 2012 ; Liu et al, 2011 ; Wang et al, 2005 ; Wang and Fu, 2008 ). The results of traditional meta-analysis were detailed in Table 7 , showed that blood urea nitrogen levels in different types of stem cell groups were lower than those in the negative control group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Em relação ao uso destas células mesenquimais no tratamento da DRC, estudos prévios de pesquisadores brasileiros (Alexandre et al, 2009;Cavaglieri et al, 2009;Donizetti-Oliveira et al, 2011;Noronha et al, 2011) e outros grupos internacionais (Peng et al, 2013) região onde ocorre o domínio da proteína quinase, por um sítio de resíduo de tirosina (Hubbard, 2004).…”
Section: Introductionunclassified